MOTIVASI KERJA DAN KEPUASAN KERJA DENGAN KINERJA PERAWAT DI RS. PKU MUHAMADIYAH GOMBONG - Suryanto Suryanto; Arimbi Dewi (Kesmas Indonesia, 2010)
Job motivation and high job satisfaction in hospitals will improve the nurse performance. This occurs when the nurses perceive intrinsic rewards and extrinsic rewards which have been received were fair and reasonable. The job satisfaction in nurses will raise motivation in the workplace so that the numbers of absence will be decreased. The job satisfaction can also improve physical and mental health status that has impact on physical fitness, high work morale and motivation so that nurse performance will be increased. How relationship between job motivation and job satisfaction with the nurse performance in PKU Muhammadiyah. This research is explanatory quantitative methods with survey and cross-sectional approach. Data analysis was performed with linear regression test. The independent variables were job motivation and job satisfaction. The dependent variable was the nurse performance. Samples were 95 nurses who worked in PKU Muhammadiyah Hospital Gombong. The research instruments use modified Likert’s scale, questionnaires and interview guides. The data sources nurses, patients and hospital manager. Nurses and hospital supported this research until research process no problems. The analysis result of ANOVA test was found F count 26.54, significance level of 0.000. with relationship value of 0.458. There was a significant positive relationship between job motivation and job satisfaction with the nurse performance of post certification ISO 9001/2008 in PKU Muhammadiyah Hospital Gombong. The closeness of relationship is moderate category. The job motivation and job satisfaction are jointly affect the nurse performance about 38.5%. The other factors were influenced, examples environment, style of leadership, job relationship and hospital’s infrastructures. The job motivation and job satisfaction were two factors that influenced the nurse performance of post certification ISO 9001/2008 in PKU Muhammadiyah Hospital Gombong. These two factors to be fluctuated so that will be increased. The job relationship managers with nurses in hospital should improved job creativity. Nurses are formal worker in hospital will be increased job creativities and competences.